Genetics Of Intervertebral Hernia And Ethnic Features Of Associations Of Col1a1 Col9a2 And Mmp3 Polymorphisms - Orzikulovich, Kobilov Azizjon; Abdurasulovich, Yusupov Shukhrat; Komilovich, Gadayev Kamoliddin (International Journal of Aquatic Research and Environmental Studies, 2026)
Degenerative diseases of the spine, including intervertebral hernias (IVH), are a pressing medical and social problem, especially among people of working age. In recent years, interest in the role of genetic factors in the pathogenesis of these conditions has increased. The article summarizes and analyzes current data on the role of COL1A1 , COL9A2 and MMP3 gene polymorphisms in the development of intervertebral disc herniations with an emphasis on ethnic characteristics and the potential significance of these markers in personalized prevention and therapy. A review of publications over the past 10 years was conducted, including molecular genetic studies, meta analyses, population and clinical studies reflecting the relationship of these genes with the risk of MPH. It has been shown that COL1A1 (rs1800012) polymorphism can reduce the biomechanical strength of the fibrous ring, COL9A2 (Trp2/Trp3) can disrupt the stability of cartilage tissue, and MMP3 (rs3025058, 5A/6A) can enhance the degradation of the extracellular matrix. The frequency of risk-associated alleles varies depending on the population, while in the population of Uzbekistan, data are limited, which emphasizes the need for local studies. Genetic markers COL1A1 , COL9A2 and MMP3 have potential diagnostic and prognostic value in assessing predisposition to intervertebral disc herniation. Their study is important for the development of personalized prevention and early diagnosis strategies, especially in ethnically heterogeneous regions such as Uzbekistan.
Keywords: Intervertebral disc herniation; COL1A1; COL9A2; MMP3; genetic polymorphism; extracellular matrix; degenerative diseases of the spine; personalized medicine; population differences; Uzbekistan.